Pengaruh Model Pembelajaran Webbed Berbantu Media Kotak Ajaib terhadap Hasil Belajar pada Pembelajaran Tematik Siswa Kelas III SD Bruder Singkawang - Christi, Maria; Hendriana, Evinna Cinda; Yanti, Lili (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This study aims to: 1). To determine the learning outcomes of third grade students of SD Bruder Singkawang in Thematic learning before using the Webbed learning model; 2). To determine the learning outcomes of third grade students of SD Bruder Singkawang in Thematic learning after using the Webbed learning model; 3) To determine how much influence the Webbed learning model assisted by the magic box media has on the learning outcomes of third grade students of SD Bruder Singkawang. The type of research is quantitative research with the pre-experimental designs (nondesigns) method, in the form of One-Group Pretest-Posttest Design. The population in this study were all third grade students totaling 89 students. The sample was taken using the purposive sampling technique. The sample selected in this study was class IIIB students, totaling 46 students. The instrument used in this study was a test of students' cognitive learning outcomes in the Indonesian and Mathematics learning content. The data analysis technique used the calculation of the final pretest-posttest score, standard deviation and effect size. The results of this study indicate that: 1) The learning outcomes of third grade students before using the webbed learning model were still relatively low. The average pretest result on the Indonesian language learning content is 60 and on the Mathematics learning content is 61. 2) The learning outcomes of grade III students before the use of the webbed learning model are still relatively low. The average pretest result on the Indonesian language learning content is 93 and on the Mathematics learning content is 86. 3) The webbed model assisted by the magic box media has a major influence on student learning outcomes in Thematic lessons in grade III of elementary school. This can be seen from the results obtained of 1.59 on the Indonesian language content and 2.85 on the Mathematics learning content. The results are included in the high criteria. So it can be concluded that there is an influence of the webbed learning model assisted by the magic box media on learning outcomes in Thematic learning of grade III students of Bruder Elementary School Singkawang.